Upaya Peningkatan Kedisiplinan Belajar Siswa Melalui Metode Reward And Punishment Pada Pembelajaran Fikih Di MTs Sarbini Alian - Arzaq, Ahmad Miftahul; Fatimah, Siti; Murtopo, Bahrun Ali (Tarbi: Jurnal Ilmiah Mahasiswa, 2022)
This study aims to improve learning discipline in Islamic Religious Education learning for class VIII students of MTs Sarbini Alian using reward and punishment learning methods. In classroom action research, it is carried out in four stages, namely the planning, implementation, observation and reflection stages. The subjects in this study were students of class VIII MTs Sarbini Alian a total of 23 students and the object in this study was student activities in the form of learning discipline. The average pre-action score is 6.5. Data collection techniques using observation and questionnaires. The instruments used are student and teacher activity observation sheets and questionnaire sheets. This research method uses quantitative and qualitative descriptive. The results showed that the use of reward and punishment learning methods can improve learning discipline in class VII students of MTs Sarbini Alian. The discipline of learning through the reward and punishment learning method of class VIII MTs Sarbini Alian increased from the first cycle of 63% to 85% in the second cycle.